Internal Medicine, Art and Science in the Third Millennium. - Muñoz Cantó, Félix (Revista Médica de Chile, 2013)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:ES-TRAD; mso-fareast-language:ES-TRAD; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–><!–[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> INTERNAL MEDICINE, ART AND SCIENCE IN THE THIRD MILLENNIUM Internal medicine, art and science in the third millennium is a statement that Medicine is not only science. It acts on the sick individual to reestablish a natural state as a curative art. Medical art, commissioned by an individual or a society, is service. It requires vocation to obtain satisfaction. However due to the incidence of value changes, market globalization, technological and industrial development, the patient/physician relationship is becoming a user/provider relationship. Physician-related factors such as a higher health care demand, resource shortage and a progressive specialization have also influenced this change of paradigm. This is causing dissatisfaction, loss of self-esteem and a lower ethical commitment among professionals. We need to recover a professional repertoire of ideas in the context of a global ethics. Responsibility and co-responsibility are ethical principles addressed to technological civilizations and their collateral effects on people and environment that lead to a “responsible globalization”. We also need a scientific futurology to define risks and avoid errors. In this era of progressive specialization, Internal Medicine, with its holistic vision of mankind, may play a fundamental role in the field of bioethics. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> <![endif]–>